Pengaruh Program Pembinaan Kondisi Fisik Terhadap Pencegahan Cedera pada Atlet - Sahabuddin Sahabuddin; Tri Angriawan (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
This study aims to determine the effect of a physical conditioning training program on injury prevention in BKMF Volleyball FIKK Universitas Negeri Makassar athletes. The research method used was quasi-experimental with a pretest-posttest design in one group. The study subjects were 30 athletes (18 males and 12 females) who participated in the physical conditioning training program for 8 weeks, with a training frequency of 3 times per week. The results showed a significant increase in all components of physical condition. The average vertical jump increased from 42.1 cm to 46.3 cm, push-ups from 18.4 times to 22.7 times, the Illinois Agility Test decreased from 17.2 seconds to 15.6 seconds, the beep test from level 6.5 to 7.8, and sit and reach from 25.3 cm to 28.9 cm. In addition, the number of injuries decreased from a total of 16 cases (8 ankles, 5 knees, 3 backs) to only 3 cases after the intervention. Statistical tests showed a significant difference between the pretest and posttest results (p < 0.05), and there was a strong negative correlation between the increase in physical condition and the decrease in the number of injuries (r = -0.65; p = 0.001). These results prove that the physical condition development program has a significant effect on reducing the number of injuries in volleyball athletes.